2022
DOI: 10.1029/2021ms002460
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Process‐Based N2O Emission Model for Natural Forest and Grassland Ecosystems

Abstract: Nitrous oxide (N 2 O) is the third most important greenhouse gas after carbon dioxide (CO 2 ) and methane (CH 4 ), with a long lifetime of ∼120 years in the atmosphere (Fleming et al., 2011). The concentration of atmospheric N 2 O has increased from 270 ppb in the preindustrial period to 332.0 ppb in 2019 (WMO, 2020), which substantially contributes to global warming as its single-molecular global warming potential is about 298 times higher than that of CO 2 (Ramanathan et al., 1985). Anthropogenic activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 158 publications
0
5
0
Order By: Relevance
“…1a ) [ 23 ]. Apart from the autotrophic nitrification and denitrifier denitrification considered in the DyN-LPJ model, the IBIS-MicN model included additional N 2 O-producing processes of heterotrophic nitrification and nitrifier denitrification [ 24 ], therefore, the IBIS-MicN model performed with a much smaller inter-annual variability. Both natural N 2 O emissions from forests and grasslands in this study are within the range of previous reports using the direct extrapolation method [ 25–28 ], linear models [ 29 ], random forest regression model [ 30 ], or process-based models [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a ) [ 23 ]. Apart from the autotrophic nitrification and denitrifier denitrification considered in the DyN-LPJ model, the IBIS-MicN model included additional N 2 O-producing processes of heterotrophic nitrification and nitrifier denitrification [ 24 ], therefore, the IBIS-MicN model performed with a much smaller inter-annual variability. Both natural N 2 O emissions from forests and grasslands in this study are within the range of previous reports using the direct extrapolation method [ 25–28 ], linear models [ 29 ], random forest regression model [ 30 ], or process-based models [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In IBIS-MicN, N 2 O emissions were simulated from four microbial N 2 O-producing processes (i.e. autotrophic nitrification, heterotrophic nitrification, nitrifier denitrification, and denitrifier denitrification) based on the dynamic activities of nitrifiers and denitrifiers, as well as local environmental conditions simulated by IBIS [ 24 ]. While DyN-LPJ simulated N 2 O emissions from autotrophic nitrification and heterotrophic denitrification based on the fully coupled carbon and N dynamics [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tao et al [39] also revealed that drip irrigation increased soil NR and NiR activities. Ma et al [40] illustrated that soil NR activity was positively correlated with soil moisture, and the higher the soil moisture, the lower the oxygen content, and the more conducive it was to the improvement of NR activity.…”
Section: Effects Of Irrigation Systems On Enzyme Activities and The A...mentioning
confidence: 99%
“…Additionally, a distribution map of maize can be used as a reference for predicting future maize distributions by exploring the driving forces of crop distribution patterns 12 . Because of the use of fertilizers such as nitrogen, a large amount of long-term existed greenhouse gas N 2 O is associated with the maize planting process 13 , 14 . Therefore, the distribution map of maize can also be an important source of data for simulating greenhouse gas emissions from agricultural ecosystems and plays an important role in determining the regional budget for greenhouse gases 15 , 16 .…”
Section: Background and Summarymentioning
confidence: 99%